1996
DOI: 10.1164/ajrccm.154.5.8912751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide inhalation on pulmonary serial vascular resistances in ARDS.

Abstract: The pulmonary vasculature site of action of nitric oxide (NO) in patients with acute respiratory distress syndrome (ARDS) is still unknown. Seven patients were studied during the early stage of ARDS. The bedside pulmonary artery single-occlusion technique, which allows estimation of the pulmonary capillary pressure (Pcap) and segmental pulmonary vascular resistance, was used without NO or with increasing inhaled NO concentrations (15 and 25 parts per million [ppm]). Systemic circulatory parameters remained una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…In contrast, animals treated with nebulized saline exhibited no significant improvement in oxygenation. The oxygenation effects noted with delivery of nebulized DMAEP/NO were similar to those observed in both animals and human subjects given continuously inhaled NO gas (10,16,(32)(33)(34). The improvement in oxygenation in the present study was probably due to improvements in intrapulmonary shunt.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, animals treated with nebulized saline exhibited no significant improvement in oxygenation. The oxygenation effects noted with delivery of nebulized DMAEP/NO were similar to those observed in both animals and human subjects given continuously inhaled NO gas (10,16,(32)(33)(34). The improvement in oxygenation in the present study was probably due to improvements in intrapulmonary shunt.…”
Section: Discussionsupporting
confidence: 82%
“…Inhaled NO has been reported in isolated perfused lungs of various species after different vasoconstrictor stimuli either to unalter the longitudinal distribution of resistances [26] or to act predominantly at precapillary level [27]. Inhaled NO did not affect the longitudinal distribution of resistances in experimental micro-embolic PH [28] but decreased the capillary-venous component of PVR in acute respiratory distress syndrome [29]. Inhaled NO diffuses easily through the alveolo-capillary membrane before its inactivation by haemoglobin, and probably dilates the smallest arterioles and venules adjacent to the alveolar space, provided there is a component of active constriction.…”
Section: Effects Of Inhaled Nitric Oxide In Pulmonary Arterial Hypertmentioning
confidence: 94%
“…Some have reported that a reduction in pulmonary water or endothelial permeability could be connected to a decrease in capillary filtration pressure [16]. However, most of the clinical studies in ARDS patients have only shown modest effects by these drugs on pulmonary capillary pressure [22][23][24], and the most recent large studies have not reported prognostic benefit with the systematic use of inhaled NO in cases of acute lung injury or ARDS [25]. Fluid restriction that is more or less associated with a diuretic treatment makes it possible to reduce both pulmonary capillary pressure and central venous pressure.…”
Section: Fluid Restriction and Diuretics: Clinical Studies And Practimentioning
confidence: 99%